Commodity Market Reforms : Lessons of Two Decades - Akiyama, Takamasa; Baffes, John; Larson, Donald; Varangis, Panos (Washington, DC: World Bank, 2013)
Structural reform of the economies of developing countries has been in the forefront of development interest since the early 1980s. This interest stems from a recognition that the structures and institutions of these countries are critical to any enhancement of economic and social development. One of the key reforms has been that of primary commodity markets, especially agricultural commodity markets, because many developing countries, including the poorest, depend heavily on these for foreign exchange earnings and employment, and hence for poverty reduction. This report focuses on the political economy and institutional aspects of agricultural commodity market reform. In order to explore in detail factors that are critical to the processes, consequences, and substance of reform, the authors have focused the analysis and evaluation on five commodities important in many developing countries, specifically cocoa, coffee, sugar, cotton, and cereal. In doing so, they highlight important lessons on how agricultural sector reform can be launched and implemented. Some of the factors identified in the report as being key to successful reform include the recognition that commodity markets often affect communities and even politics, that the initial conditions of markets are critical, and that government intervention can crowd out private sector initiatives, especially when it comes to building the institutions needed to develop a healthy agricultural sector.